Nodemcu Based Prototype Tool for Noise Detection - Florentinus Nino; Azahari; Awang Harsa Kridalaksana (TEPIAN, 2021)
Application of Prototype A tool for detecting noise based on NodeMCU is a prototype that can be used to detect sound noise and provide a warning if the sound exceeds the reasonable threshold that humans hear. The function of this system is to detect sound noise using the Analog Sound sensor V2. Then the data from the Analog Sound sensor V2 will be displayed in the form of a Led and if it has passed the threshold that humans hear, it will trigger turning on the buzzer as a warning and send automatically the decibel value, status and also if we want to check how much noise there is, we can type / telegram the sensor . Based on the data analysis carried out, Basically programming for building Prototype Tool for detecting noise based on NodeMCU using the C programming language with the help of Arduino IDE software and monitoring it using LED and Telegram. This research was made in order to facilitate controlling the noise in the environment.